Dynamical analysis of winter terrain park jumps - McNeil, J. A.; McNeil, J. B. (Sports Engineering, 2009)
Jump features in winter terrain parks frequently pose a hazard to patrons and may represent a significant liability risk to winter resorts. By performing a simple dynamic analysis of terrain park jumps, the relative risk to impact injuries for any proposed jump design can be quantified thereby allowing terrain park designers to minimize the risk from this class of injury.